Board independence and managerial authority - Dah, Mustafa (2018)
Purpose The imposition of the Sarbanes Oxley Act and the NYSE/NASDAQ regulations boosted the proportion of independent directors serving on corporate boards. For certain firms, increasing the number of independent directors may impose costs that exceed the benefits. This paper examines the implications of increased independence following SOX, relative to the pre-SOX board independence benchmark, on managerial authority and entrenchment within the firm. Design/methodology/approach Data are collected from COMPUSTAT, ExecuComp, and RiskMetrics. Data are divided into two periods, pre-SOX (1996-2001) and post-SOX (2002-2006). The focus is on the sub-group of firms who were not complying with the board independence requirement prior to SOX and became compliant afterwards. Various regressions are employed to assess the implications of increased independence following SOX on managerial authority and entrenchment. Findings The appreciation in board independence post-SOX significantly inflates both managerial compensation and the likelihood of CEO duality. Also, there is a positive association between board independence and managerial entrenchment during both the pre- and post-SOX periods. Imposed board composition requirements diminished board monitoring efficiency and boosted the CEO dominance and control over the firm. Originality/value This research adds to the extant literature investigating the implications of SOX on internal monitoring and governance. The results are based on an off equilibrium phenomenon in which companies were obliged to alter their endogenously determined board structure. Thus, regulations to improve governance could backfire as the CEO might abuse them to extract private benefits.